The reproduction of inequality in Turkey: Power distribution in a primary class - Tombak-Ilhan, Busra; Gunduz, Mustafa (SAGE PUBLICATIONS LTD, 2023)
This paper aims to understand the nature of classrooms, power containers in Gidden's words (Giddens, 1986, p.136), in terms of inequality and power share. Inequalities in education have been a by-passed subject in Turkey for a long time, and classroom practices remained black boxes (Mehan, 1979, p.4). Thus, after a brief summary of power issue in education, educational inequality discussions and their reflections in the Turkish context are discussed in the study. Then, the position teachers hold is discussed with references to history and society. Then, the 6-month observations and interviews conducted on the first grade are discussed both chronically and thematically. Beginning on the first day of school, the teacher held a higher position than the students and parents and distributed power share among students. Students were discriminated against according to their parents and cultural capital (language, strategies, communication style, and school materials). In accordance with the neoliberal policies, middle-class students and their parents were fronted in the classroom and they had more power than the others. However, lower-class students had little power and they were mostly criticized in the classroom. The strategies and advantages middle-class students had over lower-class ones are discussed in the study.
Keywords: power relations; inequality in education; social class; ethnography; primary education; TEACHERS; EDUCATION; STUDENTS; WORLD; Education & Educational Research